IDENTIFIKASI JENIS DAN TINGKAT KERUSAKAN JALAN PADA SISTEM JARINGAN JALAN PERKOTAAN - Muh Akbar; Herbin Betaubun; Chitra Utary; Dina Limbong Pamuttu; Daud Andang Pasalli (Teknik Sipil, Politeknik Negeri Ketapangg, 2023)
Jalan Arafura in Merauke Regency is an access road often passed by the general public to carry out their daily activities that should be in good condition. However, many of these roads were damaged, be they heavily, moderately, or lightly damaged. This study aimed to determine the type of damage to the asphalt surface and the value of asphalt damage on Jalan Arafura. The process of evaluating the level of road damage is calculated using the PCI (Pavement Condition Index) method. Data collection uses a survey method, and the data that has been collected includes measuring road dimensions and measuring road damage. Data collection was carried out on Jalan Arafura STA 0+035 - STA 0+525 with a length of 525 meters. The results showed that the road damage on Jalan Arafura included loose grains, holes, longitudinal cracks, transverse cracks, collapse, block cracks, and side cracks. Based on calculations using the PCI (Pavement Condition Index) method, the road condition value for Jalan Arafura is 6.6, which classifies the level of damage to the failed road pavement.